PROFESSIONAL SELF-ESTEEM DEVELOPMENT IN NURSING - Torres, Alexandra; Sanhueza, Olivia (Investigación y Educación en Enfermería, 2008)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This article analyses from an historical perspective life experienced events in nursing and their effects in professional self esteem, ﬁrst as caregivers and later as nurses. The article critically reﬂects about facts that stamped the practice of nursing during every one of its historical evolution phases: domestic, vocational, technical and professional; and how those facts could have inﬂuenced and how still inﬂuence the development of professional self- esteem. The principal problems of each phase are analysed in order to present some change proposals to improve the situations considered.